An Analysis of the Stacking Potential and Efficiency of Plant-Microbial Fuel Cells Growing Green Beans (Vigna ungiculata ssp. sesquipedalis) - Kristopher Ray Simbulan Pamintuan; Angelika Michelle C. Katipunan; Patricia Ann O. Palaganas; Alvin R. Caparanga (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
Plant-Microbial Fuel Cell (PMFC) technology is a promising bioelectrochemical system that can exploit natural plant rhizodeposition to generate electricity. PMFCs can be used to simultaneously generate electricity while growing edible plants, as illustrated in this study. However, the common problem encountered for soil PMFCs is the low power output. To solve this problem, the stacking behavior of PMFCs was examined to maximize the power output of several cells. A grid of 9 PMFCs (3x3) was constructed with stainless steel and carbon fiber electrodes growing green beans (V. ungiculata spp. sesquipedalis) for stacking purposes. Stacking results have shown that too many cells connected in series will result in voltage losses, while stacking in parallel conserves voltage between cells. Stacking a maximum of 3 cells in series is acceptable based on the results, since cumulative stacking revealed that voltage reversals can reduce the overall potential of the stack if there are too many connected cells. Stack combinations were also tested, resulting in an enhanced performance upon combining series and parallel connections allowing power to be amplified and power density to be conserved. The combination of three sets of three cells in series stacked in parallel (3S-P) generated the highest power and power density (160.86 μW/m2) amongst all combinations, showing that power amplification without losses to power density are possible in PMFC stacking. Overall, proper stacking combinations have been shown to greatly affect the performance of PMFCs. It is hoped that the results of this study will contribute to the efforts of applying PMFC technology on a larger scale.